2017
DOI: 10.1111/1365-2664.13007
|View full text |Cite
|
Sign up to set email alerts
|

Reef accessibility impairs the protection of sharks

Abstract: Reef sharks are declining world‐wide under ever‐increasing fishing pressure, with potential consequences on ecosystem functioning. Marine protected areas (MPAs) are currently one of the management tools used to counteract the pervasive impacts of fishing. However, MPAs in which reef sharks are abundant tend to be located in remote and underexploited areas, preventing a fair assessment of management effectiveness beyond remoteness from human activities. Here, we determine the conditions under which MPAs can eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 59 publications
3
69
2
2
Order By: Relevance
“…Large and migratory sharks are examples, but there may be other taxa where movements and spatial needs are less ob vious and poorly studied. Sharks, for example, respond to no-entry and not just no-take management (Claydon 2004, Robbins et al 2006, McCook et al 2010, Juhel et al 2018. Other large-space requiring bony fish species may also be influential in estimating maximum biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large and migratory sharks are examples, but there may be other taxa where movements and spatial needs are less ob vious and poorly studied. Sharks, for example, respond to no-entry and not just no-take management (Claydon 2004, Robbins et al 2006, McCook et al 2010, Juhel et al 2018. Other large-space requiring bony fish species may also be influential in estimating maximum biomass.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large survey of reef fish in fisheries closures found that many large top-level predators were virtually absent or too uncommon to sample accurately when closures were located close to fisheries markets (Cinner et al 2018). Yet other studies have shown that the combination of protection from fishing and isolation from human influ-ences can support high biomass and large roaming predators such as sharks (Stevenson et al 2007, McCauley et al 2012, Edgar et al 2014, Bradley et al 2017, Juhel et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…They often have a high intrinsic vulnerability to fishing due to slow population growth ( 9 ), and with shark products such as dried fins reaching high commercial value (up to $1697 kg −1 ), they have a high exposure to international trade ( 10 ). Throughout the Pacific, the density of reef sharks has declined to 3 to 10% of prehuman levels ( 11 ), and even the most well-managed marine protected areas appear inadequate in maintaining healthy shark populations ( 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reported biomass in closures is lower, possibly 2 times lower, than reports in the very few remaining wilderness seascapes of the Indian Ocean (Friedlander et al., ; Graham & McClanahan, ). These differences are caused by greater numbers of large‐bodied and roaming species, including groupers, jacks, snappers, sweetlips and shark populations, in wilderness than closures (Bradley et al., ; Juhel et al., ; McCauley et al., ; Nadon et al., ). Populations of these taxa decline with very low levels of fishing effort, and most closures in fished landscapes do not sustain large‐bodied and space requiring species (Graham et al., ; McClanahan, Graham, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the practical need is great, the high diversity and spatial heterogeneity of reef fishes may preclude finding useful sustainability benchmarks. For example, the maximum biomass of fish has been reported over large ranges and often associated with isolation from human influences and the existence of large roaming predators, such as sharks (Bradley et al., ; Juhel et al., ; McCauley et al., ; Stevenson et al., ). Further, large differences in biomass exist between remote wilderness and unfished national parks, indicating that human disturbance is widespread and not just limited to local fishing impacts (Graham & McClanahan, ).…”
Section: Introductionmentioning
confidence: 99%